Mirabegron and Anticholinergics in the Treatment of Overactive Bladder Syndrome: A Meta-analysis - Sartori, Luisa Gracio Ferreira; Nunes, Bruno Monteiro; Farah, Daniela; Oliveira, Leticia Maria de; Novoa, Claudia Cristina Takano; Sartori, Marair Gracio Ferreira; Fonseca, Marcelo Cunio Machado (Revista Brasileira de Ginecologia e Obstetrícia / RBGO Gynecology and Obstetrics, 2023)
Objective To compare the use of mirabegron with anticholinergics drugs for the treatment of overactive bladder (OB).Data Source Systematic searches were conducted in EMBASE, PUBMED, Cochrane, and LILACS databases from inception to September 2021. We included RCTs, women with clinically proven OB symptoms, studies that compared mirabegron to antimuscarinic drugs, and that evaluated the efficacy, safety or adherence.Data Collection RevMan 5.4 was used to combine results across studies. We derived risk ratios (RRs) and mean differences with 95% CIs using a random-effects meta-analytic model. Cochrane Collaboration Tool and GRADE was applied for risk of bias and quality of the evidence.Data Synthesis We included 14 studies with a total of 10,774 patients. Fewer total adverse events was reported in mirabegron group than in antimuscarinics group [RR 0.93 (0.89–0.98)]. The risk of gastrointestinal tract disorders and dry mouth were lower with mirabegron [RR 0,58 (0.48–0.68); 9375 patients; RR 0.44 (0.35–0.56), 9375 patients, respectively]. No difference was reported between mirabegron and antimuscarinics drugs for efficacy. The adherence to treatment was 87.7% in both groups [RR 0.99 (0.98–1.00)].Conclusion Mirabegron and antimuscarinics have comparable efficacy and adherence rates; however, mirabegron showed fewer total and isolated adverse events.
Keywords: antimuscarínicos; metanálise; mirabegrom; bexiga hiperativa